RANCANG BANGUN SISTEM INFORMASI PENCARIAN DATA MAHASISWA DAN DOSEN PADA FAKULTAS HUKUM UNIVERSITAS PALANGKA RAYA - Putu Bagus Adidyana Anugrah Putra; Viktor Handrianus Pranatawijaya; Widiatry Widiatry; Lisa Lisa (Universitas Palangka Raya, 2018)
The development of the internet is now increasingly extensive. That can be provide the easeto search and find all the information and interact or communicate with others quickly. Users cansearch the information at the search engine by input the keyword which is related to the informationby using web browser or other devices such as android applications that are being developednowadays. Android technology is a very popular technology nowadays to connect with every personwithout being limited by time and place flexibly. Users can search data online through the providedapplication system. The search data includes profiles of students or lecturers and history studies oflecture activities that have been taken.In developing this application system using PHP programming language, Android Studio,MySQL database and WSDM method (Web Site Design Method) with 5 (five) stages. These stagessuch as, (1) Mission Statement Specification. At this stage determined goals, subjects and targets ofthe website. (2) User Modeling Stage (Audience Modeling) is divided into, User Classification(Audience Clasification) and User Characteristics (Audience Characterization). (3) The ConceptualDesign stage is divided into Task Information Modeling and Navigation Design. (4) TheImplementation Design stage is divided into Site Structure Design, Presentation Design and LogicalDatabase Design. (5) And the last stage is implementation.Testing the system using blackbox testing to show that this system can be function inaccordance with the function of each feature created, and the output results are displayed inaccordance with the data entered. The process of working this system consists of data inputprocess, update data through the process of synchronization with KRS application database.Synchronized data are students, lecturers and lectures consisting of (course, grade, class,student activity, graduate student list) and then stored in database and export data to Ms.Excel.